Parents' voices: "Our process of advocating for our child with autism." A meta‐synthesis of parents' perspectives. (23rd August 2017) - Boshoff, K.; Gibbs, D.; Phillips, R. L.; Wiles, L.; Porter, L.
Abstract: Background: Advocacy has been described by parents of children with autism as an important coping strategy, enabling them to move forward by redirecting emotions into actions. A key factor in the development of collaborative and constructive partnerships between service providers and parents is having an understanding of how parents engage in advocacy and the support needed to do so. This meta‐synthesis was undertaken to consolidate in‐depth qualitative data from parents' perspectives of the process that they use to advocate for their children with autism. Methods: A qualitative meta‐synthesis was conducted, whereby 15 databases were systematically searched. Thirty‐one studies were identified and appraised using an adapted version of the Critical Appraisal Skills Programme tool. Data were synthesized into themes through the steps of review, meta‐aggregation, integration, and interpretation. Results: The voices of 1, 662 parents are presented describing the process of advocacy in the stages of seeking a diagnosis, seeking self‐education, and taking action. Taking action includes 2 subthemes: seeking, access, and use of support services and community engagement and educating others. Conclusions: Results highlight the significant impact that positive experiences with first‐line professionals have during the diagnosis process and how these experiences lay the foundation for all future relationships with other service providers. Important implications arise from this meta‐synthesis for service providers in supporting parents' advocacy and hence building constructive relationships with families with a child with autism.